A study of the impact of major Urban Heat Island factors in a hot climate courtyard: The case of the University of Sharjah, UAE. (June 2021) - Mushtaha, Emad; Shareef, Sundus; Alsyouf, Imad; Mori, Taro; Kayed, Assel; Abdelrahim, Marwa; Albannay, Shamma
Highlights: Urban Heat Island (UHI) factors were identified and categorized. Analytical hierarchy process and ENVI-met simulation were used to evaluate UHI factors' effectiveness. AHP results showed that the most effective factor in the environmental category is air movement, in the urban category is urban greenery, and in the building category, is building material. ENVI-met results showed that the most effective building factor is the aspect ratio. The best combination of building factors reduced the temperature by 2.45 °C. Abstract: Urban development in urban areas accommodates a high concentration of human activities. The constant state of evolution in these urban areas is accompanied by environmental problems, including the formation of the Urban Heat Island effect (UHI), where the air is hotter than in rural areas. This research investigates where they occur the factors that contribute to the UHI by reviewing the previous literature on the subject and dividing the factors according to what has created them: 1) the wider environment, 2) their general urban surroundings, and 3) the specific buildings around them. Locally, it has been found that very few publications have covered the factors that compose UHI. Therefore, this study aims to support previous literature on this subject by adopting a novel approach and using two research methods to rank the most important UHI factors. In the first stage of the study, on the subjective basis of experts' opinions, the Analytical Hierarchy Process (AHP) was used to rank the UHI factors and, thus, identify the most important factor in each category. In the second stage of the study, this process was extended to test the hierarchy of UHI factors in an existing courtyard, which included most of the relevant factors in its design and construction. After developing proposed scenarios in the courtyard, ENVI-met simulation software was used to test and evaluate each factor. The scenarios were developed around factors from the building category and this resulted in another ranking, based on each factor's contribution to reducing the surface temperature. The more effective factors were together applied to three optimized scenarios and finally the outdoor surface temperature was reduced by 2.45 °C, partly by the best combination of the most effective factors to be identified.